Library service quality survey for Pustaka Miri / Voon Boo Ho ... [et al.] - Voon, Boo Ho; Sabil, Hayati; Moss, Izaruddin; Samsudin, Ahmad (2008)
A systematic evaluation of service providers is essential in ensuring effective policymaking and operations management. The continuous as well as comprehensive understanding and monitoring-ofstrategic domain, such-as service quality, is essential since service providers such as libraries should perform according to changing markets emanating from technological advancements, customer needs and regulatory policy. Rendering consistent excellent service is believed to be one of the keys for survival and success. Pustaka Negeri Sarawak (Kuching) and now Pustaka Miri are among the pioneering state libraries in this region which have successfully undertaken a large-scale exercise employing multiple approaches to improve the quality of its services towards library excellence.